Use of an electronic patient-reported outcome measure in the management of patients with advanced chronic kidney disease: the RePROM pilot trial protocol. Issue 10 (28th October 2018) - Kyte, Derek; Bishop, Jon; Brettell, Elizabeth; Calvert, Melanie; Cockwell, Paul; Dutton, Mary; Eddington, Helen; Hadley, Gabby; Ives, Natalie J; Jackson, Louise J; Stringer, Stephanie; Valente, Marie
Abstract : Introduction: Chronic kidney disease (CKD) affects up to 16% of adults in the UK. Patient quality of life is particularly reduced in end-stage renal disease and is strongly associated with increased hospitalisation and mortality. Thus, accurate and responsive healthcare is a key priority. Electronic patient-reported outcome measures (ePROMs) are online questionnaires which ask patients to self-rate their health status. Evidence in oncology suggests that the use of ePROM data within routine care, alongside clinical information, may enhance symptom management and improve patient outcomes. However, National Health Service (NHS)-based ePROM research in CKD is lacking. This pilot trial will assess the feasibility of undertaking a full-scale randomised controlled trial (RCT) in patients with CKD within the NHS. Methods and analysis: The renal ePROM pilot trial is an investigator-led single-centre, open-label, two-arm randomised controlled pilot trial of 66 participants ≥18 years with advanced CKD. Participants will be randomised to receive either usual care or usual care supplemented with an ePROM intervention. Participants within the intervention arm will be asked to submit monthly self-reports of their health status using the ePROM system. The system will provide tailored information to patients in response to each report and notify the clinical team of patient deterioration. The renal clinical team will monitor for ePROM notifications and will respond with appropriate action, in line with standard clinical practice. Measures of study feasibility, participant quality of life and CKD severity will be completed at 3 monthly intervals. Health economic outcomes will be assessed. Clinicians will record treatment decision-making. Acceptability and feasibility of the protocol will be assessed alongside outcome measure and intervention compliance rates. Qualitative process evaluation will be conducted. Ethics and dissemination: The findings will inform the design of a full-scale RCT and the results will be submitted for publication in peer-reviewed journals. The study has ethical approval. Trial registration numbers: ISRCTN12669006 ; Pre-results.